Children's Self-Control through Play Methods and Interactive Activities for 7-10 Year Olds: Self-Control Anak melalui Metode Bermain dan Kegiatan Interaktif Usia 7–10 Tahun - Ramadhan, Asya Afifa Putri; Kamila, Nadia Nashwa; Fatikawardhani, Dinda; Hapsara, Astri A. (Psikologia : Jurnal Psikologi, 2025)
This research was conducted using play methods and interactive activities that aim to improve self-control skills in children aged 7-10 years in RPTRA West Jakarta. Self-control is an important aspect that must be developed early on so that children are able to think logically, manage emotions, and make decisions independently. For three weeks we have implemented an intervention program with a total of ﬁve main activities; (a) Mewarnai; (b) Berburu Harta Karun; (c) Daur Ulang Jadi Karya; (d) Jendela Perasaanku; dan (e) Layar Ceria. Measurement was carried out using the pre-test and post-test method, which is a measurement with a self-control questionnaire. The analysis showed a signiﬁcant increase in the three dimensions of self-control, namely behavioral control, cognitive control, and decisional control. Therefore, game-based interactive activities are proven to be eﬀective in improving children's self-control as a whole. Highlights: Effective Intervention: Game-based interactive activities significantly improved children's behavioral, cognitive, and decisional self-control. Structured Program: The intervention included five engaging activities—coloring, treasure hunting, recycling, emotional expression, and screen-based storytelling. Measured Impact: Pre-test and post-test analysis confirmed measurable growth in self-control among children aged 7–10 in RPTRA West Jakarta. Keywords: Self-Control, Children, Play Method, Interactive Activities